SELIMUT ANTI API INOVASI PENCEGAHAN DAN MITIGASI KEBAKARAN TAHAP AWAL BERSAMA MITRA PBKM KESUMA MARELAN MEDAN - Suyanti, Retno Dwi; Pardosi, Sri Masnita; Nasution, Alvi Sahrin; Prima, Heppy Setya (Universitas Mataram, 2025)
Fires are sudden disasters that can cause significant losses, both material and non-material. Prompt early response is crucial to prevent the spread of fire, but many communities lack simple and easy-to-use fire extinguishers. A five-member community service team, in collaboration with the Kesuma Community Learning Center (PKBM), led by Ms. Siti Nurhayati, located in Lk 2 Pasar 2 Barat Terjun, Medan Marelan, and involving 40 community members as partners, conducted training and developed an innovation called a